2017
DOI: 10.1155/2017/8107140
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Epidoxorubicin Hydrochloride in Aqueous Solutions: Experimental and Theoretical Studies

Abstract: The first-order degradation kinetics of epidoxorubicin were investigated as a function of pH, temperature, and buffers concentrations. The degradation was followed by HPLC. Buffer catalysis was observed in acetate and phosphate buffers. The pH-rate profiles were obtained at 333, 343, 353, and 363 K. The pH-rate expression was pHwhere 1 , 4 , and 5 are the second-order rate constants (mol −1 L s −1 ) for hydrogen ion activity and for hydroxyl ion activity, respectively, and 2 and 3 are the first-order constants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…An electrophile radical prefers electron-efficient locations whereas a nucleophile radical favours the electron-deficient positions to attack in the species [42]. It is already reported that the system with a high value of dipole moment will show intense aqueous solvation because of superior interface with the dipole moments of the adjoining water molecules [27]. Epirubicin and epoprostenol show the maximum and minimum value of electrophilicity index respectively.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…An electrophile radical prefers electron-efficient locations whereas a nucleophile radical favours the electron-deficient positions to attack in the species [42]. It is already reported that the system with a high value of dipole moment will show intense aqueous solvation because of superior interface with the dipole moments of the adjoining water molecules [27]. Epirubicin and epoprostenol show the maximum and minimum value of electrophilicity index respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Sobczak et al . [28] have examined the reactivity of epidoxorubicin in solid as well as in solutions with different pH values. Samide et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation